Living Standards and Productivity - Burkhead, Jesse (The Review of Economics and Statistics, 1951)
THE decade of the I940'S brought a phenomenal increase in the of living of the people. Common observation bears this out; available data permit its quantification. When per capita disposable personal income adjusted for price changes is used as the best measurement of the standard of living, it would appear that the lot of the average American was about 30 per cent better in I949 than in I940 2 A series showing per capita real incomes is published periodically by the Council of Eco-